The Drackenberg adventure - Alexander, Lloyd (New York : Dell, 1988)
In 1873 seventeen-year-old Vesper Holly and her guardians travel to an obscure European grand duchy, where their archenemy Dr. Helvitius is pursuing a lost art treasure and engineering the country's annexation by a neighboring kingdom.
Booklist.
Children's Catalog (Wilson).
Junior High School Library Catalog (Wilson).
5.3
5-8.
Keywords: Adventure and adventurers -- Fiction; Adventure and adventurers -- Fiction